T7 RNA Polymerase Bypass of Large Gaps on the Template Strand Reveals a Critical Role of the Nontemplate Strand in Elongation - Zhou, Wei (1995)
We show that T7 RNA polymerase can efficiently transcribe DNA containing gaps from one to five bases in the template strand. Surprisingly, broken template strands missing up to 24 bases can still be transcribed, although at reduced efficiency. The resulting transcripts contain the full template sequence with the RNA deleted for the gapped region missing on the template strand. These findings indicate that the end of a downstream template strand can be brought into the polymerase and transcribed as if it were a part of an intact polynucleotide chain by utilizing the unpaired nontemplate strand. This, as well as transcription of an intact template strand, relies heavily upon the nontemplate strand, suggesting that a duplex DNA-binding site on the leading edge of RNA polymerase is required for RNA chain elongation on DNA templates. This work contributes substantially to the emerging picture that the nontemplate strand is an important element of the transcription elongation complex.